Protease-activated receptor-2 activation: A major role in the pathogenesis of Porphyromonas gingivalis infection - Holzhausen, Marinella; Spolidorio, Luis Carlos; Ellen, Richard P.; Jobin, Marie-Claude; Steinhoff, Martin; Andrade-Gordon, Patricia; Vergnolle, Nathalie (Elsevier, 2006)
We have investigated the specific contribution of protease-activated receptor-2 (PAR2) to host defense during Porphyromonas gingivalis infection. Culture supernatants from P. gingivalis strains 33277 and W50 provoked Ca2+ mobilization in cells transfected with PAR2 (PAR2-KNRK) and desensitized the subsequent responses to PAR 2-selective agonist. In addition, culture supernatants of P. gingivalis E8 (RgpA/RgpB double knockout) did not cause calcium response in PAR2-KNRK cells, evidencing the involvement of the arginine-specific cysteine proteases RgpA and RgpB in PAR2 activation by P. gingivalis. Injection of P. gingivalis into mouse subcutaneous chambers provoked an increased proteolytic activity, which was inhibited by serine protease inhibitors. Fluids collected from chambers of P. gingivalis-injected mice were able to activate PAR2 and this activation was inhibited by serine protease inhibitors. P. gingivalis inoculation into subcutaneous chambers of wild-type mice induced an inflammatory response that was inhibited by a serine protease inhibitor and was significantly reduced in PAR2-deficient mice. Finally, mice orally challenged with P. gingivalis developed alveolar bone loss, which was significantly reduced in PAR2-deficient mice at 42 and 60 days after P. gingivalis infection. We conclude that PAR2 is activated on P. gingivalis infection, in which it plays an important role in the host inflammatory response. Copyright © American Society for Investigative Pathology.